Maize Empty Pericarp602 Encodes a P-Type PPR Protein That Is Essential for Seed Development. (10th May 2019) - Ren, Zhenjing; Fan, Kaijian; Fang, Ting; Zhang, Jiaojiao; Yang, Li; Wang, Jianhua; Wang, Guoying; Liu, Yunjun
Abstract: Pentatricopeptide repeat (PPR) proteins play crucial roles in intron splicing, which is important for RNA maturation. Identification of novel PPR protein with the function of intron splicing would help to understand the RNA splicing mechanism. In this study, we identified the maize empty pericarp602 ( emp602 ) mutants, the mature kernels of which showed empty pericarp phenotype. We cloned the Emp602 gene from emp602 mutants and revealed that Emp602 encodes a mitochondrial-localized P-type PPR protein. We further revealed that Emp602 is specific for the cis -splicing of mitochondrial Nad4 intron 1 and intron 3, and mutation of Emp602 led to the loss of mature Nad4 transcripts. The loss of function of Emp602 nearly damaged the assembly and accumulation of complex I and arrested mitochondria formation, which arrested the seed development. The failed assembly of complex I triggers significant upregulation of Aox expression in emp602 mutants. Transcriptome analysis showed that the expression of mitochondrial-related genes, e.g. the genes associated with mitochondrial inner membrane presequence translocase complex and electron carrier activity, were extensively upregulated in emp602 mutant. These results demonstrate that EMP602 functions in the splicing of Nad4 intron 1 and intron 3, and the loss of function of Emp602 arrested maize seed development by disrupting the mitochondria complex I assembly.